Development and implementation of CHEMIDIA: A digital support system for distance chemistry practicum in high schools - Rahmah, Nani; Cahyana, Ucu; Hanafi, Ivan (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to develop and implement Chemidia, a web-based application designed to support remote and blended chemistry practicums in high school settings. It focused on the application’s features, its impact on student preparedness, and student perceptions of its effectiveness. Using a Design-Based Research (DBR) approach, Chemidia was developed through iterative phases: needs analysis, design, testing, and implementation. The platform includes four core features: Chemical Inventory Management, Safety Protocol Access, Chemistry Experiment Modules, and Self-Directed Learning Tasks. Implementation involved 89 students in a blended learning environment, with data collected through surveys, interviews, and observations. Survey results showed significant improvements in students’ practicum preparedness (mean increased from 3.1 to 4.2), understanding of safety protocols (3.3 to 4.4), and confidence in conducting experiments (2.9 to 4.1). Over 82% of students strongly agreed that Chemidia improved their understanding. TAM-based evaluations indicated high perceived usefulness and ease of use. Qualitative feedback reinforced these findings, highlighting enhanced student autonomy, clarity, and engagement. Chemidia effectively supports chemistry practicum learning in hybrid environments by improving student readiness, self-efficacy, and instructional continuity. This study presents Chemidia as a scalable model for integrating digital tools into science education. It offers practical insights for educators and developers aiming to enhance laboratory learning through blended or remote delivery formats.